The Reaction of Ethylenediamine with 1, 4‐Bis(trimethylsilyl)butadiyne and the Role of Water: A Qualitative Method for the Determination of Water Impurities in Ethylenediamine. Issue 20 (16th May 2019) - Frischhut, Sabine; Bentlohner, Manuel M.; Fässler, Thomas F.
Abstract : Alkenylation of [Ge9 ] 4– and formation of the vinylated species [Ge9 (CH=CH2 ) n ] (4– n )– proceed only in ethylenediamine ( en ) as a solvent. Variation of the alkyne leads to coupling products between the alkyne and en . Herein, we investigated the coupling reactions between 1, 4‐bis(trimethylsilyl)butadiyne and en and showed that a water impurity in en plays a decisive role in the outcome of the reaction. NMR spectroscopic investigations revealed that 1‐trimethylsilyl‐7‐amino‐5‐aza‐hepta‐3‐en‐1‐yne is formed by addition of en at 1, 4‐bis(trimethylsilyl)butadiyne. Addition of another amino‐functionality of en giving both the cyclization product and 1, 9‐di‐amino‐4‐methyl‐3, 7‐di‐aza‐nonadiene is only possible in presence of water. 1, 9‐Di‐amino‐4‐methyl‐3, 7‐di‐aza‐nonadiene is also formed by the reaction of deprotonated en with 1‐trimethylsilyl‐7‐amino‐5‐aza‐hepta‐3‐en‐1‐yne. Based on these results, we developed a simple method to detect water in en, supported by 1 H NMR spectroscopy. The finding that 1, 9‐di‐amino‐4‐methyl‐3, 7‐di‐aza‐nonadiene is also formed by reaction of 1‐trimethylsilyl‐7‐amino‐5‐aza‐hepta‐3‐en‐1‐yne with deprotonated en was exploited to indirectly proof the deprotonation of en upon the nucleophilic reaction of [Ge9 ] 4– with alkynes in the solvent en . Abstract : The reaction of ethylenediamine ( en ) with 1, 4‐bis(trimethylsilyl)butadiyne is presented and the formation of different reaction products depending on the water‐content in en is discussed. Based on the results, a simple method to trace water in en, supported by 1 H NMR spectroscopy was developed.